Brain areas with normatively greater cerebral perfusion in early life may be more susceptible to beta amyloid deposition in late life - Meier, Irene B.; Lao, Patrick J.; Gietl, Anton; Vorburger, Robert S.; Gutierrez, José; Holland, Christopher M.; Guttmann, Charles R.G.; Meier, Dominik S.; Buck, Alfred; Nitsch, Roger M.; Hock, Christoph; Unschuld, Paul G.; et al. (Cerebral circulation - cognition and behavior, 2020)
•Brain areas with higher neuronal activity and metabolic demand in early life may contribute to higher beta amyloid deposition later in life.•The spatial relationship between normative perfusion patterns in young individuals and amyloid pathophysiology in older individuals were assessed.•Brain areas with normatively greater perfusion may be more susceptible to amyloid deposition in later life. The amyloid cascade hypothesis characterizes the stereotyped progression of pathological changes in Alzheimer's disease (AD) beginning with beta amyloid deposition, but does not address the reasons for amyloid deposition. Brain areas with relatively higher neuronal activity, metabolic demand, and production of reactive oxygen species in earlier life may have higher beta amyloid deposition in later life. The aim of this study was to investigate early life patterns of perfusion and late life patterns of amyloid deposition to determine the extent to which normative cerebral perfusion predisposes specific regions to future beta amyloid deposition. One hundred twenty-eight healthy, older human subjects (age: 56–87 years old; 44% women) underwent positron emission tomography (PET) imaging with [11C]PiB for measures of amyloid burden. Cerebral perfusion maps derived from 47 healthy younger adults (age: 22–49; 47%) who had undergone single photon emission computed tomography (SPECT) imaging, were averaged to create a normative template, representative of young, healthy adults. Perfusion and amyloid measures were investigated in 31 cortical regions from the Hammers atlas. We examined the spatial relationship between normative perfusion patterns and amyloid pathophysiology. The pattern of increasing perfusion (temporal lobe<parietal lobe<frontal lobe<insula/cingulate gyrus<occipital lobe; F(4,26)=7.8, p = 0.0003) in young, healthy adults was not exactly identical to but approximated the pattern of increasing amyloid burden (temporal lobe<occipital lobe<frontal lobe<parietal lobe<insula/cingulate gyrus; F(4,26)=5.0, p = 0.004) in older adults. However, investigating subregions within cortical lobes provided consistent agreement between ranked normative perfusion patterns and expected Thal staging of amyloid progression in AD (Spearman r = 0.39, p = 0.03). Our findings suggest that brain areas with normatively greater perfusion may be more susceptible to amyloid deposition in later life, possibly due to higher metabolic demand, and associated levels of oxidative stress and inflammation.